Charismatic Authority and Transformative Da’wah: the Leadership of K.H Thoifur Mawardi in Pesantren-Based Community Empowerment - Fauzi, Ach; Zulfa Elizabeth, Misbah; Sulthon, Muhammad (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This article examines charismatic authority in pesantren-based da'wah, a dimension of Islamic education leadership that remains underexplored. While Max Weber’s concept of charisma has been widely applied in political and organizational studies, its relevance to Indonesian pesantren leadership is rarely addressed. Taking KH Thoifur Mawardi of Daarut-Tauhid, Purworejo, as a case study, this research analyzes how charisma operates as both personal virtue and institutional capital in sustaining transformative da'wah. A qualitative approach was employed through interviews, participant observation, and documentation, with triangulation ensuring data credibility. The study shows that KH Thoifur’s charisma, rooted in moral integrity, Islamic scholarship, and emotional proximity to the community, enables him to mobilize spiritual awareness, social solidarity, and pesantren-based economic initiatives. Although limited to a single institution, the study critically adapts Weber’s notion of charisma to the pesantren context, offering a contextual framework that links leadership, spirituality, and social change. It concludes that effective da'wah must be participatory, human-centered, and sustainable to address contemporary challenges.